Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.14221/ajte.2014v39n11.8
|View full text |Cite
|
Sign up to set email alerts
|

Navigating E-Learning and Blended Learning for Pre-service Teachers: Redesigning for Engagement, Access and Efficiency

Abstract: Nebulous combinations of face-to-face and online learning are increasingly common across Australian higher education contexts. This paper reports on part of a redesign project of an undergraduate education subject at a regional university. The aim of the redesign was to enhance e-learning and blended learning environments. An approach that maps the evaluation research activities to the design and development cycle of e-learning tools and learning tasks was adopted (Phillips et al., 2012). The research took a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 7 publications
(19 reference statements)
2
29
0
Order By: Relevance
“…However, from a pedagogical standpoint, additional intervention strategies included: to clearly outline participation requirements of the course, to ask questions addressing the integration of ideas, and to play a visible role in guiding students towards the achievement of learning goals (Pawan et al 2003). By placing more responsibility on the students to drive their own learning (Forbes and Khoo 2015;Regan et al 2012), the role of the teachers in effective online environments was more about facilitation than about knowledge transfer (Chigeza and Halbert 2014). Some teachers also provided students with the opportunity to perform as discussion moderators (Chieu, Herbst, and Weiss 2011;Phirangee 2016), enhancing their active role in the online process and making them coresponsible of both their own and peers' learning.…”
Section: The Teaching Presencementioning
confidence: 99%
“…However, from a pedagogical standpoint, additional intervention strategies included: to clearly outline participation requirements of the course, to ask questions addressing the integration of ideas, and to play a visible role in guiding students towards the achievement of learning goals (Pawan et al 2003). By placing more responsibility on the students to drive their own learning (Forbes and Khoo 2015;Regan et al 2012), the role of the teachers in effective online environments was more about facilitation than about knowledge transfer (Chigeza and Halbert 2014). Some teachers also provided students with the opportunity to perform as discussion moderators (Chieu, Herbst, and Weiss 2011;Phirangee 2016), enhancing their active role in the online process and making them coresponsible of both their own and peers' learning.…”
Section: The Teaching Presencementioning
confidence: 99%
“…The re-shaping of the curriculum that blended learning encompasses should support students' capacity for independent learning and the students should be at the centre of the curriculum planning (Chigeza & Halbert, 2014). Educators should aim to develop higher order skills such as critical and creative thinking, organisation and motivation to enhance thinking processes, learning opportunities and knowledge application.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It can be challenging to create link between the online activities and the physical activities in school campus (35) , (36) . Some research also suggests that an overarching pedagogical frame, explicit scaffolding of learning activities through podcasts and other appropriate media, hands-on assessment tasks and regular communication between student and staff are vital for creating a better learning environment for students (37) . https://www.indjst.org/ Many studies have demonstrated the role played by the teacher in facilitating online learning, such as supporting technological efficacy (38) and facilitating content comprehension (39) .…”
Section: Results Of the Teacher Surveymentioning
confidence: 99%